2020
DOI: 10.1186/s12944-020-1186-1
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for lipid profile in Iranian children and adolescents: the CASPIAN-V study

Abstract: Background: We aimed to develop the age-and sex-specific reference values for lipid profile of Iranian pediatric population. Methods: Fasting lipid profiles of 3843 participants, aged 7 to 18 years, were extracted from a surveillance survey on Iranian children and adolescents living in 30 provinces across the country. Results: The mean (SD) age of participants was 12.3(3.1) years, and 52.3% of them were boys. Significant differences were observed between genders comparing the levels of triglyceride (TG) (P = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
1
6
1
Order By: Relevance
“…Te fndings of our study demonstrated that concentrations of TC, LDL, and non-HDL were signifcantly higher in girls compared to boys. Our observations of higher TC and LDL-C levels in girls compared with boys were similar to the HELENA study in the European adolescents [25]; a study of healthy Indian school children and adolescents [26], and the CASPIAN-V study [18], while Lopez et al did not observe any gender diferences in the Fuenlabrada study [27]. In Brazilian school children and adolescents, girls also had greater values of TC and LDL-C compared to boys [28].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Te fndings of our study demonstrated that concentrations of TC, LDL, and non-HDL were signifcantly higher in girls compared to boys. Our observations of higher TC and LDL-C levels in girls compared with boys were similar to the HELENA study in the European adolescents [25]; a study of healthy Indian school children and adolescents [26], and the CASPIAN-V study [18], while Lopez et al did not observe any gender diferences in the Fuenlabrada study [27]. In Brazilian school children and adolescents, girls also had greater values of TC and LDL-C compared to boys [28].…”
Section: Discussionsupporting
confidence: 88%
“…Previously, two studies have reported the lipid reference values in Iranian children and adolescents [18,32]. In comparison with the CASPIAN-V study, the mean values of HDL in both genders, TC, non-HDL, and LDL in girls were higher and TG was lower in the present study.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This is in agreement with other investigations. 12 , 23 Given the different effects of sex hormones on lipid and lipoprotein components, this observation could be ultimately construed. There are significant sex differences in lipid and lipoprotein metabolism that contribute to sex differences.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported usefulness of this index in a range of values from 1.4 to 2.9 (Krawczyk et al 2018;Acosta-García and Concepción-Páez 2018;Behiry et al 2019;Özalp Kızılay et al 2019;Azizi-Soleiman et al 2020) in obese children from different parts of the world. The cut-off point of 2.4 found in our study is closer to the point reported in the Latin American population by Acosta et al (Acosta-García and Concepción-Páez 2018), which was 2.25, which suggests that genetics play an important role in the behavior of lipid metabolism from early stages of life.…”
Section: Discussionmentioning
confidence: 99%